8-quinolylcyclopentadienyl, a ligand with a tailored fit for chelate complexes - Enders, Markus; Rudolph, Ralph; Pritzkow, Hans (Chemische Berichte - recueil, 1996)
8-Lithioquinoline reacts with 2,3,4,5-tetramethylcyclopentenone to give 8-quinolylcyclopentadiene (1/2) after acidic workup and treatment with ammonia. Two of the possible three isomers are formed; the acidic protons on the Cp rings show unusual downfield shifts in the 1H-NMR spectra. Treatment with strong bases led to the intensely coloured anionic 4 which was converted into the trimethylsilyl derivative 5. This is a suitable starting compound for the trihalotitanium and -zirconium compounds 6 and 7. The two complexes were investigated by crystal structure analyses. In both cases the quinolyl nitrogen atom is coordinated to the metal.